2016
DOI: 10.1089/gyn.2015.0057
|View full text |Cite
|
Sign up to set email alerts
|

Management of Giant Ovarian Cysts: A Review of 5 Case Reports

Abstract: Background: Articles on giant ovarian cysts have become less common in medical literature. These cysts mimic ascites, presenting with abdominal distension and shifting dullness. They are predominantly serous and mucinous cystadenomas. Rare cases of low-grade of malignant tumors and adenocarcinomatous ovarian cysts have been reported. Materials and Methods: This was a retrospective descriptive study of 5 cases recruited between 2009 and 2012. The selected patients had large ovarian cysts extending to the epigas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It is reported that over 70% of these tumors are benign. They are said to be mainly serous or mucinous cyst 3,12,13 adenomas. Malignancies are less common (20-25%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that over 70% of these tumors are benign. They are said to be mainly serous or mucinous cyst 3,12,13 adenomas. Malignancies are less common (20-25%).…”
Section: Discussionmentioning
confidence: 99%
“…However, when the tumor grows from been a pelvic mass to not just an abdominal-pelvic mass but up to the epigastric region, abdominal pains from cyst accidents and obstruction with associated nausea, vomiting, early satiety, constipation, respiratory difficulty etc could be some of the presenting features of 2,3 the affected patient. If not properly evaluated, the gross abdominal distention could be diagnosed to be massive 3,4,5 ascites such as the case reported by Yeika et al Most of these tumors are benign serous or mucinous cyst adenomas; although few cases of low-grade malignant 3 (adenocarcinomas) have been diagnosed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant ovarian tumors are a known entity, but very rare in developed countries given that most ovarian masses are discovered early on routine medical visits. Most reported cases are from developing regions such as India [ 3 ] or Africa [ 4 ]. Mucinous cystadenomas are typically unilateral, benign tumors of epithelial origin lined by tall columnar, non-ciliated epithelial cells with apical mucin and basal nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Gynecologists shouldn't ignore clinical, ultrasonographic, biochemical and possible MRI evaluation of patients [9]. Imaging is paramount for planning management of giant ovarian cysts as imaging identifies any suspicious features of malignancy e.g., multiple partitions, and endo-or exocystic vegetations [16]. Moreover, meticulous intraoperative naked-eye assessment of the ovary and the ipsilateral ovary are good assuring steps.…”
Section: Author Contributionmentioning
confidence: 99%